Mission Statements as a Basis for Reflection on the Priorities of the General Secondary School - Urszula Dernowska (The Francis de Sales Scientific Society (TNFS.PL), 2021)
The article provides an analysis of general secondary school mission statements of 53 schools from the public sector in Warsaw. The purpose of the study was to gain a perspective on the school's priorities as defined by secondary schools themselves. The qualitative content analysis revealed that mission statements highlight the broad range of goals that the schools pursue. Some of these goals may be thought of in terms of educational results, while others may be seen as educational "inputs". The obtained results show that schools share certain priorities, but there was also a range of "specific" objectives that the educational institutions pursue.